MOLECULAR IDENTIFICATION AND MORPHOLOGICAL CHARACTERIZATION OF PATCHOULI (Pogostemon sp.) FROM BATANG REGENCY, CENTRAL JAVA PROVINCE - Aeldo Yudifian; Anto Budiharjo; Rejeki Siti Ferniah; Hermin Pancasakti Kusumaningrum (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
Patchouli (Pogostemon cablin Benth.) is an essential oil-producing plant from Batang Regency that has excellence in patchouli alcohol contents and highly survives in any condition. Molecular identification has been done in the ITS region because DNA sequences in the ITS rRNA region evolved faster than in other areas. This study aimed to get the molecular and morphological identity of patchouli (Pogostemon sp.) from BPP Kabupaten Batang. The study consisted of sample preparation, DNA isolation, amplification, electrophoresis, sequence data analysis, and phylogenetic analysis using MEGA X. All parts of plant were morphologically identified and compared with patchouli from Sidikalang, Aceh, Java, and China. Extraction DNA produced 301.7 ng ?L–1 concentration and 1.93 purity. Amplification of ITS fragment patchouli produced a 670 bp-sized single band. Phylogenetic analysis showed patchouli BPP related to Pogostemon cablin (KR608752.1) with 98% coverage identity. BPP patchouli showed 62,5% morphological similarity with Sidikalang patchouli compared to Java patchouli. In conclusion, BPP patchouli is a Sidakalang patchouli P. cablin that has undergone environmental adaptation. Nilam (Pogostemon cablin Benth.) adalah tanaman atsiri dari Kabupaten Batang dengan keunggulan berupa kandungan patchouli alcohol dan ketahanan hidup yang tinggi. Identifikasi molekuler dilakukan pada daerah ITS karena sekuens DNA pada daerah ITS rRNA berevolusi lebih cepat dibandingkan daerah gen lain sehingga akan bervariasi pada setiap spesies. Penelitian ini bertujuan memperoleh identitas molekuler dan morfologi tanaman nilam (Pogostemon sp.) dari BPP Kabupaten Batang. Penelitian ini terdiri dari penyiapan sampel, isolasi DNA, amplifikasi fragmen ITS, elektroforesis, sekuensing, analisis data sekuens, analisis filogenetik menggunakan MEGA X. Morfologi seluruh bagian tanaman diidentifikasi dan dibandingkan dengan nilam dari Sidikalang Aceh, Jawa, dan Cina. Isolasi DNA nilam menghasilkan konsentrasi 301,7 ng µL–1 dan kemurnian 1,93. Amplifikasi fragmen ITS nilam menghasilkan pita tunggal 670 bp. Hasil identifikasi molekuler diikuti dengan analisis filogenetik menunjukkan nilam BPP Kabupaten Batang berkerabat dekat dengan P. cablin (KR608752.1) sebesar 98%. Hasil identifikasi morfologis nilam BPP memperlihatkan 62,5% persamaan morfologi dengan nilam Sidakalang dibandingkan dengan nilam Jawa. Kesimpulan, nilam BPP merupakan nilam Sidakalang P. cablin yang telah mengalami adaptasi lingkungan.